2015
DOI: 10.1136/bmjquality.u207871.w3816
|View full text |Cite
|
Sign up to set email alerts
|

Improving timely medical reviews for patients discharged from intensive care

Abstract: Transferring patients from the intensive care unit (ICU) to a general ward is commonly associated with error and adverse events, and is one of the most challenging and high-risk transitions of care. Patients discharged from ICUs often require sustained intensive multi-disciplinary team input, part of which can be provided by nurse or clinician-led outreach teams. Unfortunately, due to a lack of resources many institutions do not have such programmes. We work in one such hospital with no ICU outreach service fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Nurses identified that one major barrier to patient portal enrolment was difficulty remembering the sign-up process in a long list of tasks necessary for ‘rooming’ a patient. Many intervention projects have used visual reminders to improve or change the behaviour of healthcare professionals 8–11. Similarly, to address this barrier, we implemented a visual reminder for the nurse to increase patient portal sign-ups.…”
Section: Designmentioning
confidence: 99%
“…Nurses identified that one major barrier to patient portal enrolment was difficulty remembering the sign-up process in a long list of tasks necessary for ‘rooming’ a patient. Many intervention projects have used visual reminders to improve or change the behaviour of healthcare professionals 8–11. Similarly, to address this barrier, we implemented a visual reminder for the nurse to increase patient portal sign-ups.…”
Section: Designmentioning
confidence: 99%